Incubating a slow pedagogy in professional academic development: An ethics of care perspective - Collett, K.S.; van den Berg, C.L.; Verster, B.; Bozalek, V. (South African Journal of Higher Education, 2018)
The current neoliberal impetus in higher education has effects on all aspects of academic life, including professional academic development. These effects include increasing workloads and more casualisation of academic work, particularly teaching and a greater emphasis on quantification of scholarly outputs. The Slow movement provides an alternative way for valuing academic life (Berg and Seeber 2016; Bozalek 2017; Hartman and Darab 2012; Martell 2014; Ulmer 2017), as does the ethics of care, which has been used as a normative framework to evaluate and re-imagine academic development from a different perspective than that of neoliberalism (Bozalek et al. 2014; Tronto 2010). To date, however, there has been little engagement with how Slow pedagogy (Berg and Seeber 2016) might be put into conversation with an ethics of care to re/configure professional academic development. Our paper addresses this gap by diffractively reading the political ethics of care (Tronto 1993; 2013) through the concept of a Slow pedagogy in order to reimagine creative provocations for academic development. Experiences of a group of participants, who attended inter-institutional academic development courses in Cape Town, are drawn upon to illustrate the superpositions of these diffractive readings. The intra-actions in face-to-face and online meetings and artefacts are analysed to see what was helpful for the development and flourishing of the small group of participants using the new insights gained through the diffractive readings. Findings show how a professional development course, informed by elements of care ethics and Slow pedagogy, enhance the sustainability of professional learning communities.